Single phase and boiling heat transfer under steady and pulsating confined jet impingement - Sridhar, Abishek (Curtin University, 2013)
Computational and experimental investigations are carried out on steady and pulsating jet impingement heat transfer. The studies focus on the fundamental investigation of heat transfer with and without boiling phenomena, applicable in the area of electronic cooling. The novelty of the research is the exploration of the relative significance of the contributing fluid and heat transport mechanisms under different parametric conditions.